Effect of Celosia cristata extract on the quality of flavoured milk during storage - SAYEED, RUKHSAAR; THAKUR, MONIKA; GANI, ADIL (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted to study the effect of addition of Celosia cristata extract on the storage stability of rose flavoured milk at Amity Institute of Food Technology, Amity University Uttar Pradesh in 2019. Different levels (0.25-1%) of C. cristata extract rich in betalains were used as natural colorant in rose flavoured milk. The product was analysed for shelf life during which it was stored under refrigerated storage for 12 days and analysed for chemical, microbiological and sensory tests at regular intervals. During storage, pH declined while the total soluble solids (TSS) increased significantly. A significant reduction in the colour, flavour and mouth feel scores was observed after 8 days of storage. Total plate count (TPC) increased in both control and CCE incorporated drinks with storage period. The increase in TPC was more in control as compared to CCE incorporated drink. Though the sensory scores also declined with storage, the CCE incorporated drink obtained good acceptability scores even after 10 days of storage at refrigeration temperature.